Indigenous Pedagogy for Developing Essential Life-Skills of Children in Masaka District, Uganda - Kavuma, Caroline Nakidde; Ejuu, Godfrey (East African Journal of Arts and Social Sciences, 2024)
Contemporary education practice is widely seen as practices that blend conventional approaches with either new innovations or culturally tested practices. In a situation where being cultural or modern has its own drawbacks, towing the middle position becomes an inevitable choice. The paper presents findings from an exploratory sequential study that examined the influence of Indigenous Pedagogy (IP) on developing children's life skills in Masaka District, Uganda. It was anchored on Lewin's (1922) change theory; likened to Manion and Cohen's (1975) reinvention theory and adopted as a restoration theory. Snow bowling, purposive and stratified random sampling were used to select 44 participants. Twenty (20) key informants including 6 parents, 2 elders, 6 religious, 2 District Education Officers; 2 Ministry officials and 2 local council leaders were interviewed. Twenty-four (24) other respondents participated in three-eight-member Focus Group Discussions (FDGs). The findings portray replicable practices of skilling based on deep-rooted beliefs set on standards that are supported by aspirations in harmony with nature. The study found that methods used by Masaka parents combined theory and practice daily; in lessons that happen where knowledge was situated, mainly through apprenticeship, attachment, heart-to-heart and one-to-one encounters. They also embraced global citizenry based on firm principles of what Africans value. The study concluded that indigenous methods were still useful in grooming children with life skills of productive work, character, positive attitudes, mental acuity and social orientation. It recommends that teacher education institutions require academic programmes blending contemporary with indigenous methods anchored on core African values to prepare pro-cultural-modern teachers. To link the valuable past to the inevitable contemporary ways of knowing, the application of hybrid pedagogy becomes imperative